2011
DOI: 10.3389/fnana.2011.00022
|View full text |Cite
|
Sign up to set email alerts
|

Topographical Organization of the Pedunculopontine Nucleus

Abstract: Neurons in the pedunculopontine nucleus (PPN) exhibit a wide heterogeneity in terms of their neurochemical nature, their discharge properties, and their connectivity. Such characteristics are reflected in their functional properties and the behaviors in which they are involved, ranging from motor to cognitive functions, and the regulation of brain states. A clue to understand this functional versatility arises from the internal organization of the PPN. Thus, two main areas of the PPN have been described, the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
188
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 208 publications
(202 citation statements)
references
References 118 publications
(186 reference statements)
11
188
0
3
Order By: Relevance
“…The PPN contains a mixed population of cholinergic, glutamatergic and GABAergic neurons 11,13,23,29 . Electrophysiologically, at least three types of neuron have been identified 31,33,39 , however, there is little correlation between cells electrophysiological properties and their neurochemical identity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The PPN contains a mixed population of cholinergic, glutamatergic and GABAergic neurons 11,13,23,29 . Electrophysiologically, at least three types of neuron have been identified 31,33,39 , however, there is little correlation between cells electrophysiological properties and their neurochemical identity.…”
Section: Discussionmentioning
confidence: 99%
“…The PPN has extensive connections with the basal ganglia 5,11 , receiving strong inhibitory inputs from both the globus pallidus internus and substantia nigra 41 . Thus, the reduction in PPN activity may be mediated by inhibitory input from the basal ganglia 41 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides being anatomically separated, each of these regions contains neurons with diverse transmitter phenotypes with excitatory long-range projection neurons –that are glutamatergic in CnF and both glutamatergic and cholinergic in PPN– intermingled with local inhibitory interneurons 11,12 . Electrical stimulation or lesion studies are therefore unable to distinguish the contribution from the various intermingled neuronal populations present in these areas 12,13 . Recently, optogenetic manipulations have showed that stimulation of glutamatergic neurons (GlutNs) in and around PPN induced locomotion in mice 14 .…”
Section: Introductionmentioning
confidence: 99%
“…Stimulation of VTA dopaminergic neurons likely works by recruiting neural circuits that involve limbic cortices, nucleus accumbens, and pedunculopontine nucleus (6,9,18). The role of other wake-active neurons in the emergence from general anesthesia (6,19) remains to be clarified, including neurons using neurotransmitter acetylcholine, histamine, norepinephrine (20), serotonin and orexin.…”
mentioning
confidence: 99%